2015
DOI: 10.4253/wjge.v7.i2.128
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic retrograde cholangiopancreatography for suspected choledocholithiasis: From guidelines to clinical practice

Abstract: The guidelines should be considered to optimize patients' selection for ERCP. For high risk patients specificity is still low, meaning that some patients perform ERCP unnecessarily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
2
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 26 publications
6
43
2
17
Order By: Relevance
“…A similar finding was made for the intermediate risk score, where both the sensitivity and positive predictive value in our series were lower than those described in published series on patients with suspected choledocholithiasis (14.4 and 41%, respectively) [9][10][11][12] .…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…A similar finding was made for the intermediate risk score, where both the sensitivity and positive predictive value in our series were lower than those described in published series on patients with suspected choledocholithiasis (14.4 and 41%, respectively) [9][10][11][12] .…”
Section: Discussioncontrasting
confidence: 46%
“…While the sensitivity of the high risk score was approximately the same as found in published series in patients with suspected choledocholithiasis overall (86%), the positive predictive value was significantly lower (52 vs. 71-79%) [9][10][11][12] . A similar finding was made for the intermediate risk score, where both the sensitivity and positive predictive value in our series were lower than those described in published series on patients with suspected choledocholithiasis (14.4 and 41%, respectively) [9][10][11][12] .…”
Section: Discussionmentioning
confidence: 63%
“…7,9,10 Al constituirse en una patología biliar de presentación atípica, recae un valor agregado el diagnóstico oportuno, para evitar el advenimiento de diversas complicaciones. 11 Es así, que la colangiorresonancia magnética se constituye en un auxiliar fundamental para visualizar el terreno en donde vamos a llevar a cabo nuestras acciones terapéuticas, con la colangiograf{ia retrógrada endoscópica como auxiliar terapéutico añadido; 12,13,16 y en cuanto al tratamiento, se demuestra que la técnica elegida fue la que menos efectos de morbimortalidad presentaba, siendo la anastomosis del colédoco al duodeno en este caso muy superior a la hepatoyeyuno anastomosis en Y de Roux por cuanto los signos de colangitis resultantes son mucho más lesivos en la segunda técnica que en la primera.…”
Section: Discussionunclassified
“…6 Para el enfrentamiento de la misma es importante conocer la ubicación, número, estado general del paciente, impactación y tamaño del cálculo; siendo el último factor una entidad clínica independiente. 7 Se considera que cuando el diámetro del lito es superior o igual a 15-20 mm, se lo denomina megalitiasis. 7 La historia clínica, exámenes de laboratorio, estudios de imagenología como ecografía, resonancia magnética nuclear, métodos diagnósticos invasivos como la colangiografia retrógrada con papilotomía, son herramientas de gran utilidad para saber cuál es la actitud más adecuada a seguir en el tratamiento de la coledocolitiasis, 8,9,10,11 más aun cuando se ha reportado fracasos en el tratamiento endoscópico con tasas de hasta el 88 % 12,13,14 y particularmente en los casos de coledocolitiasis con cálculos de gran tamaño.…”
Section: Introductionunclassified
“…In Europe, ultrasound studies revealed a prevalence of 9-21% and an incidence of 0.63/100 persons/year [1][2][3][4] . Choledocholithiasis or common bile duct (CBD) stones are a frequent complication of gallstone disease and are pres-stones [4] .…”
mentioning
confidence: 99%